Pseudomyxoma Peritonei: A Retrospective Study of Patients with Unexplained Granulomas - Huma Aslam, Muhammad Azhar Qureshi, Saqib Qayyum, Muhammad Khan Malik, Sirajuddin, Saifullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pseudomyxoma peritonei (PMP) is a rare malignancy characterized by mucinous ascites and peritoneal involvement. While granulomas are typically associated with infectious and inflammatory diseases, their presence in PMP remains poorly understood. Objective: This study aims to evaluate the occurrence, histopathological characteristics, and clinical significance of unexplained granulomas in PMP patients. Methods: This retrospective study conducted at Jinnah postgraduate medical center Karachi during January 2021 to January 2022. It included 65 patients diagnosed with PMP who exhibited granulomas in histopathological specimens. Clinical, radiological, and histopathological data were analyzed. Granulomas were categorized as caseating or non-caseating and further classified as foreign body-type or immune-mediated. Results: Non-caseating granulomas were more common (60%) than caseating granulomas (40%), with 72.3% of granulomas associated with mucin deposits. Peritoneal involvement was observed in 89.2% of patients, with omental caking in 67.7% and visceral scalloping in 49.2%. Cytoreductive surgery was performed in 90.8% of cases, achieving complete cytoreduction in 69.5%, while HIPEC was administered to 78.5%. Survival analysis revealed that caseating granulomas were associated with significantly lower five-year survival (47.3%) and higher recurrence rates (p = 0.033), whereas non-caseating and foreign body-type granulomas showed better outcomes. Patients with granulomas had a higher recurrence rate (43.1%) and lower overall survival (61.5%) than those without granulomas (36.2% recurrence, 70.2% survival), with a significant p-value of 0.046. Conclusion: It is concluded that granulomas in PMP are likely a reactive immune response rather than an infectious process. The presence and type of granulomas may have prognostic significance, with caseating granulomas indicating a more aggressive disease course. Keywords: Pseudomyxoma peritonei, granulomas, peritoneal malignancy, survival analysis, histopathology, prognosis.